Penerapan Jaringan Distribusi Sistem District Meter Area (DMA) SPAM Semarang Barat dalam Optimalisasi Penurunan Kehilangan Air Ditinjau dari Aspek Teknis dan Finansial (Studi Kasus : Area Pelayanan Reservoir Manyaran 1) - Bagus Tri Buko; Anik Sarminingsih; Budi Prasetyo Samadikun (School of Postgraduate Studies, Diponegoro Univer, 2022)
Drinking water is one of basic human needs that is very important to improve the quality of human life and economic growth of a region. PDAM Tirta Moedal, Semarang City developed “SPAM Semarang Barat” 1,000 liters/sec to serve water demand in West Semarang, Ngaliyan and Tugu sub-districts. Water losses in PDAM Kota Semarang is still at 40.10%, indicating that water distribution is not optimal. DMA is a strategy in managing water loss, especially real water loss, by dividing an open water supply network into isolated zones with smaller water meter. In this study, a technical and financial study was conducted regarding the implementation of DMA in the SPAM Semarang Barat distribution specifically for the Manyaran 1 Reservoir service area . The real water loss is caused by visible or invisible leakage of distribution pipes (background leakage). The billed authorized consumption is estimated at 4,189,607 m3/year, the unbilled authorized consumption is 7,361 m3/year. Apparent water loss is estimated at 147,455 m3/year or about 2%, while real water loss is around 2,172,896 m3/year or about 34%. The Infrastructure Leakage Index or ILI for the Manyaran 1 Reservoir distribution is 49. It means that PDAM is wasting some resource, which caused losses. Epanet 2.0 shows that peak hours pressure is between 30 – 70 m, there is no pressure below 10 m. Velocity at peak hours is in the range of 0.1 – 1.0 m/s. The investment requirement for DMA development in the Manyaran 1 service area Rp. 18,786,292,828, - for development of services as much as 5,843 SR. District Meter Area in distribution system is estimated to reduce the leakage rate by up to 20%, so that the potential revenue will increase by Rp. 26,083,764,633,-. It means that DMA is one of ways to solve water leakage problem.